2022
DOI: 10.3390/nano12132189
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Carvacrol-Loaded Caseinate/Zein-Composite Nanoparticles Using the Anti-Solvent Precipitation Method

Abstract: Extending shelf life and maintaining the high quality of food are arduous challenges. In this study, the self-assembly properties of zein were used to load carvacrol essential oil, and then sodium caseinate was selected as a stabilizer to fabricate carvacrol-loaded composite nanoparticles. The results showed that the composite nanoparticles had a high encapsulation efficiency for carvacrol (71.52%–80.09%). Scanning electron microscopy (SEM) indicated that the carvacrol-loaded composite nanoparticles were spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Compared with our published studies [ 34 ], the composite NPs prepared in this study have better structure and performance. Published studies have used the antisolvent precipitation method to prepare CA-loaded composite NPs.…”
Section: Discussionmentioning
confidence: 65%
“…Compared with our published studies [ 34 ], the composite NPs prepared in this study have better structure and performance. Published studies have used the antisolvent precipitation method to prepare CA-loaded composite NPs.…”
Section: Discussionmentioning
confidence: 65%
“…It was found that the smaller the average particle size of the emulsion, the larger the specific surface area, 18 and the smaller the PDI, the more uniform the particle size distribution. 19 Hence, the minimum average particle size and minimum PDI were set as constraints. The optimal formulation of SE-OPEO was determined to be OPEO/Triton X-100/ IPA (10/52.5/37.5, w/w/w), and the average particle size and PDI were predicted to be 12.10 nm and 0.192, respectively.…”
Section: Preparation Of Materialsmentioning
confidence: 99%
“…According to the Ostwald–Freundlich equation, decreasing the particle size of organic materials further to the nanorange has exhibited higher solubility in poor solvents, enabling the applications of high-performance small molecules as ink materials for printing processes in optoelectronic devices. The solubility of materials in various solvents serves as the basis for the solvent–antisolvent method, which is the most straightforward and commonly used approach for preparing nanoparticles. …”
Section: Introductionmentioning
confidence: 99%